Evaluating Cultural Hallucinations in Multimodal Generative AI: A Transparency and Trustworthiness Perspective (International Journal of Artificial Intelligence Engineering and Systems, 2026)
The rapid advancement of multimodal generative artificial intelligence has introduced capabilities for synthesizing images, text, and video with unprecedented fidelity. While substantial effort has focused on factual hallucinations in language models and object-level hallucinations in vision-language systems, a more insidious class of failure remains underexamined: cultural hallucination, defined as the systematic distortion, stereotyping, or erasure of cultural symbols, practices, and visual identities. This paper provides a system-level analysis of cultural hallucinations through the intertwined lenses of transparency and trustworthiness. We argue that cultural hallucinations arise not merely from insufficient data representation but from a confluence of architectural design choices, opaque curation pipelines, and evaluation protocols that prioritize object-centric accuracy over culturally grounded semantic fidelity. Drawing on interdisciplinary literature spanning machine learning, science and technology studies, and algorithmic auditing, we examine how contrastive pre-training objectives, dataset homogenization, and prompt-to-image decoding amplify hegemonic visual narratives. We further assess the limitations of existing transparency instruments, including model cards and datasheets, in capturing culturally specific failure modes, and propose extensions that incorporate culture-aware auditing, participatory red-teaming, and interpretability probes sensitive to symbolic meaning. Deployment-level consequences are analyzed, highlighting how cultural hallucinations erode public trust, perpetuate symbolic marginalization, and constrain the safe integration of generative models into education, media, and cross-cultural communication. We conclude by outlining a governance and research infrastructure framework that treats cultural veracity as a first-class dimension of model trustworthiness, calling for multi-stakeholder observatories, culturally stratified evaluation benchmarks, and continuous monitoring mechanisms that transcend static accuracy metrics.
Keywords: cultural hallucination, multimodal generative AI, transparency, trustworthiness, cultural representation, text-to-image generation, algorithmic auditing, socio-technical systems